2018
DOI: 10.1186/s12969-018-0281-6
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity in patients with oligo- and polyarticular juvenile idiopathic arthritis diagnosed in the era of biologics: a controlled cross-sectional study

Abstract: BackgroundKnowledge about objectively measured levels of physical activity (PA) and PA participation (included facilitators and barriers for PA) in patients with juvenile idiopathic arthritis (JIA) diagnosed in the era of biologics is limited. We aimed to compare objectively measured PA in patients with oligo- and polyarticular JIA diagnosed in the biologic era with controls and to examine associations between PA and disease variables; furthermore, to explore participation in PA, physical education (PE) and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 37 publications
(65 reference statements)
1
20
4
Order By: Relevance
“…The latter is potentially important as advances in medical therapies could have an impact on physical fitness. Contrary to previous studies, our research group recently reported that objectively measured PA levels were comparable between patients with JIA and controls from the general population ; indicating that it would be informative to evaluate physical fitness in the same cohort. The aims of the present study were 3‐fold and included comparing physical fitness in patients with JIA who were diagnosed in the era of biologics with age‐ and sex‐matched controls from the general population, comparing physical fitness in patients with persistent oligoarticular JIA and those who had polyarticular disease to examine if disease severity is still of importance, and exploring associations between physical fitness and different disease variables.…”
Section: Introductioncontrasting
confidence: 95%
See 3 more Smart Citations
“…The latter is potentially important as advances in medical therapies could have an impact on physical fitness. Contrary to previous studies, our research group recently reported that objectively measured PA levels were comparable between patients with JIA and controls from the general population ; indicating that it would be informative to evaluate physical fitness in the same cohort. The aims of the present study were 3‐fold and included comparing physical fitness in patients with JIA who were diagnosed in the era of biologics with age‐ and sex‐matched controls from the general population, comparing physical fitness in patients with persistent oligoarticular JIA and those who had polyarticular disease to examine if disease severity is still of importance, and exploring associations between physical fitness and different disease variables.…”
Section: Introductioncontrasting
confidence: 95%
“…We believe our findings suggest that JIA‐related disease factors no longer have an impact on physical fitness when multidisciplinary patient care is given in the era of biologics, but further studies are needed. Studying the same cohort, we have previously found comparable overall physical activity levels between patients and controls , which we believe contribute to our findings of no associations between disease variables and physical fitness.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Overall outcomes of rheumatic diseases (RD) in childhood have improved substantially due to new treatment programs, including the use of biologic agents and methotrexate combined with physical activity (1)(2)(3)(4). Children and parents must administer most of these drugs via regular needle injections.…”
Section: Introductionmentioning
confidence: 99%